3rd ICTs and Society Meeting; Paper Session - Inequalities: social, economic, political; Paper 3: Internet in China: Myths and Realities - Bichler, Robert and Gaderer, Eva (tripleC: Communication, Capitalism & Critique. Open Access Journal for a Global Sustainable Information Society, 2010)
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEyNjkvdHJpcGxlYy52OGkyLjIxOQ